Commitments and the Marital Match: The Effect of Alimony Reform on Assortative Matching - Daniel Fernández-Kranz; Jennifer Louise Roff (Institute of Labor Economics (IZA), 2021)
This paper examines the effects of reforms that reduced alimony on matching in the marriage market. Recent literature indicates that divorce law changes which reduce commitment or income-sharing upon separation will lead to an increase in assortative matching, as women forgo specialization which may not be compensated upon divorce. Using state-level data on alimony reform that reduced the entitlements of eligible spouses and American Community Survey data on marriage and the characteristics of newlyweds, we find that alimony reform increased measures of spousal covariance in education. Our results indicate that correlation coefficients on spousal degree attainment consistently rise with alimony reform, and regression-based measures of assortative matching increase similarly. Moreover, we find the largest effects among those groups who might be more sensitive to the reform. Regression-based measures of assortative matching increase by over 10% among couples in which at least one partner had previously been married and by 9% among those couples who marry in states with less generous property division and child support which are often treated as substitutes for alimony in divorce settlements.
Keywords: J12; K12; 330; marriage; matching; divorce law; alimony; assortative matching; commitment mechanisms